Assessment of the Phytotoxic Effects and Ecological Risks to Phaseolus vulgaris Planted on Crude Oil Spiked Soils - Ogeleka, Doris F.; Bokolo, Patrick C.; Omoregie, Gloria O. (Tanzania Journal of Science, 2020)
Crude oil can contaminate environmental matrices during extraction, production, refining, loading and offloading. This study evaluated the phytotoxic effects and ecological risks to beans (Phaseolus vulgaris) planted on native soils spiked with concentrations of crude oil with a secondary aim to phytoremediate the soil. The results showed a decrease in plant heights (60.80 ± 2.11 to 25.30 ± 1.10 cm), leaf areas (40.00 ± 1.70 to 23.60 ± 1.40 cm2), leaf number (14.00 ± 0.00 to 8.00 ± 0.00), and stem girth (1.57 ± 0.06 to 1.33 ± 0.06 cm) with increasing crude oil concentrations. The total petroleum hydrocarbons (TPH) indicated that 30.2%, 21.4% and 7.6% of crude oil were removed from 1000 mg/kg (0.1%), 10000 mg/kg (1%) and 100000 mg/kg (10%) crude oil contaminated soil in addition to that taken up by the plants (10.8%, 8.6% and 0), respectively. Considerable differences between the treatment groups and the controls were measured at levels of P = 0.05. The plant Phaseolus vulgaris had bio-remediative potentials–ability to absorb the pollutants, however, its efficacy to hyper-accumulate will take a considerable period, probably several months to years to phyto-remediate a small percentage of toxicants (crude oil) in the soil.